Ogólne kierunki rozwoju nauki o handlu wewnętrznym w Polsce Ludowej - Zakrzewski, Zbigniew (Wydział Prawa i Administracji UAM, 1980)
Dominating tendencies marked out in a socio-economic policy have been conventionally accepted as a basis of a review of achievements of internal trade science in the Peopled Poland in subsequent periods. A proper share of particular sectors, i.e. of the state, co-operative and private (sectors, in the whole trade activity was among others the subject of live interests of the science and of economic publicism in the years of economic reconstruction (1945 - 1949). In the period of the Six-Year Plan realization (1.950 - 1055) new separate trade disciplines emerged, that served with their scientific achievements to the needs of developing socialist trade. The disciplines concentrated their efforts on all problems of shaping trade organization. An essential progress in recognition of a market mechanism, conditions of consumer's demand and the most important economic and organizational aspects of turnover of commodities was strongly marked in the years of principal changes in the economic policy (1956 - 1970). Interests were devoted also to theory of trade and new concepts within that scope put forward: The still developing scientific discussion on appraisal, of commodity turnover functioning gave push, especially in the seventies, to new ideas tending to adjust properly organizational structure of consumers goods market as well as its systems of planning and management with consumers' needs and preferences. It allowed in turn to introduce problems of modern marketing in a broad approach.
General Development Directions of the Science of Internal Trade in the People's Poland